Spór o realizm 1945–1948 - Mackiewicz, Paweł (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2020)
The polemic over understanding realism and its usefulness in literature was given birth in the early post-war years out of the need to refer to the rich tradition of Great Realism. This was to be a remedy to the problems with the literary presentation of current events and recent history, especially the war years and occupation as well as helping in ‘balancing the ledger’ in the Polish interbellum. The interest in realism swiftly reached beyond literature itself, while the polemic also moved onto the canvas of paining and the plastic arts. In the context of the polemic over realism there evolved also other disputes in the period 1945–1948 such as the discussion on the work Lalka. The subject of polemic under discussion in the present study ebbed and flowed over the columns above all the publications Kuźnica and Odrodzenie, but also Twórczość and Tygodnik Powszechny. Taking part in this exchange of viewpoints was a broad community of literary critics representing a greatly varied kaleidoscope of esthetics and beliefs. Among those clinking swords were Jan Kott, Kazimierz Wyka, Adam Ważyk, Stefan Żółkiewski, Artur Sandauer, Stefan Kisielewski and Melania Kierczyńska.
The Polemic over Realism, 1945–1948